GC-MS Analysis and In Vivo Antimalarial Activities of Seed Extract and Solvent Fractions of Telfairia occidentalis in Plasmodium berghei-infected Mice - Sunday, Nsikakabasi Enefiok; Osigwe, Chinyelu Clementina; Enin, Godwin Ndarake; Uwaeme, Ugonma Florence; Essien, Grace Emmanuel; Okokon, Jude Efiom (Sciences of Pharmacy, 2026)
Telfairia occidentalis Hooke. F. (Cucurbitaceae family), a vegetable whose parts are used for both nutritional and medicinal purposes was investigated for anti-malarial activity in mice. The dried seed powder was separately cold extracted in 50% ethanol and gradient solvents (n-hexane, dichloromethane, ethyl acetate and methanol) along polarity gradient to obtained crude ethanol extract and solvents fractions of T. occidentalis seed. Based on previously established median lethal dose, the seed extract (138-553 mg/kg) and solvents fractions (276 mg/kg) were investigated for in vivo activity against Plasmodium berghei infection in mice using suppressive, prophylactic and curative standard models. Gas chromatography-mass spectroscopy (GC-MS) analysis of the active fraction was also done to identify its chemical constituents. The seed extract and fractions (138-553 mg/kg, p.o.) exerted significant (p < 0.05–0.001) chemosuppressive activity against P. berghei infection in suppressive (65.67%; 18.33 ± 3.71 days), prophylactic (55.39%; 17.66 ± 2.18 days) and curative (77.48%; 18.00 ± 1.15 days) tests with methanol fraction having the highest activity. GC-MS analysis of the active methanol fraction revealed the presence of polyunsaturated fatty acids and monoterpenes which have been implicated previously in antimalarial activity of plants. These results revealed the strong antimalarial potentials of the methanol seed fraction and its phytochemical constituents which can be exploited in the development of antimalarial remedies.